Numerical analysis of blast pressure parameters on RC wall with circle opening - Mohammad Fazriel, Zaidi (2019)
Reinforced concrete (RC) wall is known as barrier wall used to protect of buildings or areas from blast loads. RC wall is the type used for protection. Further study is needed to investigate blast overpressure due to the explosive with 13.61 kg (30 lbs.) TNT equivalent weight in blast field area. Present work aim to determine the effect on the blast pressure parameters due to the solid RC wall and solid RC wall with circle opening at 1219 mm standoff distance from the centre of the charge weight as an equivalent mass of Trinitrotoluene (TNT) by using Finite Element (FE) software, AUTODYN. The RC wall has a cross-sectional dimension of 1829 mm x 1219 mm with wall thickness of 152 mm and 305 mm thickness of strip footing. The blast overpressure analysis divided to four parts. The first part present the blast overpressure analysis of 13.61 kg (30 lbs.) TNT charge weight at located 5486 mm (18 ft.) away on the free-field space. The charge weight are located at 1219 mm (4 ft.) away from the centre of the RC solid wall. This research compared the blast overpressure parameters as reported by Yan et al. (2011) of the blast overpressure parameters. The second part present the blast overpressure analysis of 13.61 kg (30 lbs.) TNT charge weight located at 1219 mm (4 ft.) away from the RC solid wall. The pressure gauge are located at 1219 mm (4 ft.), 2438 mm (8 ft.), 3657 mm (12 ft.), 4876 mm (16 ft.) and 5486 mm (18 ft.) away from the charge weight. The third part shows the blast overpressure analysis of 13.61 kg (30 lbs.) TNT charge weight at located at 1219 mm (4 ft.) away from the RC wall with 25% of circle opening while fourth part also similar to the third part but replaced with RC solid wall with 50% of circle opening. The pressure gauge based on second and third part are located similarly based on the location of pressure gauge from second part. From the result of the blast overpressure analysis, the blast overpressure between RC solid wall (Type 2), RC solid wall with 25% of circle opening (Type 3) and RC solid wall with 50% of circle opening (Type 4) are similarly in the term of blast pressure parameters. It is because of the type of the RC wall have similar criteria and properties of the designation. Therefore, the RC solid wall are possible to replace with RC solid wall with circle opening (25% or 50%) because it can save the cost of the percentage of concrete but still with same in the term of blast pressure parameters. RC wall with circle opening give more aesthetic value and economical to be as protection in the term of blast pressure parameters. RC wall also possible to use another shape of opening such as rectangle, square, triangle and others that will give more effective in the term of blast pressure parameters. The percentage of opening that used for this research are 25% and 50% of circle opening. So, for next research it can suggested with 30% or 60% of circle opening to get more efficiently based on the blast overpressure analysis.